2012
DOI: 10.1002/humu.22205
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Deletion inSMPXCauses a Rare form of X-Linked Progressive Hearing Loss in Two Families Due to a Founder Effect

Abstract: X-linked hearing loss is the rarest form of genetic hearing loss contributing to <1% of cases. We identified a multiplex family from Newfoundland (Family 2024) segregating X-linked hearing loss. Haplotyping of the X chromosome and sequencing of positional candidate genes revealed a novel point deletion (c.99delC) in SMPX which encodes a small muscle protein responsible for reducing mechanical stress during muscle contraction. This novel deletion causes a frameshift and a premature stop codon (p.Arg34GlufsX47).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The molecular genetics associated with the 99delC SMPX mutation carried by the DFNX4 families described in this article have been reported in detail in a previous publication (Abdelfatah et al, 2013). In our DFNX4 families, the auditory phenotype for male carriers of this mutation is a bilateral, symmetrical, sensorineural hearing loss with progression from a mild impairment to a severe or profound high frequency loss by middle age.…”
Section: Dfnx4: Smpx Genementioning
confidence: 79%
See 2 more Smart Citations
“…The molecular genetics associated with the 99delC SMPX mutation carried by the DFNX4 families described in this article have been reported in detail in a previous publication (Abdelfatah et al, 2013). In our DFNX4 families, the auditory phenotype for male carriers of this mutation is a bilateral, symmetrical, sensorineural hearing loss with progression from a mild impairment to a severe or profound high frequency loss by middle age.…”
Section: Dfnx4: Smpx Genementioning
confidence: 79%
“…These clinical data were combined with prospective family interview data provided by relatives participating in the study; some phenotype data used for chromosome-wide mapping was reported previously (Abdelfatah et al, 2013). Pedigrees were drawn with a pedigree software program (Progeny Inc.), and auditory phenotypes associated with specific SMPX and POU3F4 genotypes were determined.…”
Section: Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…All probands recruited to the study were screened for population-specific deafness alleles (Supplementary Table 1; Abdelfatah et al 2013a, b; Ahmed et al 2004; Doucette et al 2009; Young et al 2001). To identify other candidate genes to screen, audiograms were submitted to Audiogene (Hildebrand et al 2009) for computerized comparison with known average audiograms of 16 autosomal dominant loci (under the assumption that hearing loss was segregating as an autosomal dominant trait in these NL families).…”
Section: Methodsmentioning
confidence: 99%
“…Religious and geographic isolation within small coastal fishing (outport) communities (Manion 1977) has resulted in a higher inbreeding coefficient in the NL population (Bear et al 1987, 1988; Zhai et al 2015). We have previously identified several founder deafness mutations in the NL populations (Abdelfatah et al 2013a, b; Ahmed et al 2004; Doucette et al 2009; Young et al 2001). …”
Section: Introductionmentioning
confidence: 99%